A theory of property - Munzer, Stephen R. (Cambridge studies in philosophy and law., 1990)
This book represents a major new statement on the issue of property rights. It argues for the justification of some rights of private property while showing why unequal distributions of private property are indefensible. Three features of the book are especially salient: it offers a challenging new pluralist theory of justification; the argument integrates perceptive analyses of the great classical theorists Aristotle, Locke, Hegel and Marx with a discussion of contemporary philosophers such as Nozick and Rawls; and the author moves with assurance among philosophy, law and economics to present a very broad, interdisciplinary study.